2003
DOI: 10.1103/physrevlett.90.235501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrostatic Pressure on Closed-Loop Phase Behavior of Block Copolymers

Abstract: The effect of hydrostatic pressure (P) on closed-loop phase behavior of deuterated polystyrene-block-poly(n-pentyl methacrylate) copolymers [dPS-PnPMA] was investigated by using small-angle neutron scattering and birefringence. For P<20.7 bar, dPS-PnPMA exhibited a lower disorder-to-order transition temperature (T(LDOT)) at 175 degrees C, and then an upper order-to-disorder transition temperature (T(UODT)) at 255 degrees C. With increasing pressure both T(LDOT) and T(UODT) were markedly changed, where dT(LDOT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 26 publications
2
52
0
1
Order By: Relevance
“…[10][11][12][13] Schwahn et al observed an abnormal pressure dependence of a phase boundary of poly͑ethylethylene͒-block-poly͑dimethylsiloxane͒, and explained it with a dominating increase in the entropic term of the Flory-Huggins interaction parameter. Pressure dependence of phase transitions in polymer blends and block copolymers has been a subject of intense research both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Schwahn et al observed an abnormal pressure dependence of a phase boundary of poly͑ethylethylene͒-block-poly͑dimethylsiloxane͒, and explained it with a dominating increase in the entropic term of the Flory-Huggins interaction parameter. Pressure dependence of phase transitions in polymer blends and block copolymers has been a subject of intense research both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure dependence of phase transitions in polymer blends and block copolymers has been a subject of intense research both experimentally and theoretically. 13 In the case of polymer-aqueous systems, polymer solutions 4, [14][15][16][17][18][19] and gels 17,20 were extensively studied in order to reveal pressure effects on solubility, and different phase behaviors between at low and high pressures were obtained. 12 Ryu et al reported a closed-loop pressure-temperature ͑P-T͒ phase curve for poly͑styrene͒-block-poly͑n-pentyl methacrylate͒.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these commercially available polymers, baroplastic is an emerging material that could potentially be applied for the use of HME in pharmaceutical proteins. Baroplastic is a type of block‐copolymers that could perform melt‐like behavior induced by pressure (Ruzette et al, 2003; Ryu et al, 2003). These polymers normally contain nanophase domains of a high glass transition temperature ( T g ) (the hard segment) and a low‐ T g component (the soft segment) (Cho, 2012).…”
Section: Challenges Still Remaining In Hmementioning
confidence: 99%
“…특히, 최근 많이 연구되고 있는 압력가소성 고분자 (baroplastic polymer) [13][14][15][16] 또한 고분자의 계면과 밀접히 연관 되어 있어, 고분자 블렌드의 역할이 기대되는 분야이다. 인가 된 압력에 의해 고분자 계면에서 상변화가 유도될 수 있는 압 력가소성은 문헌에 17 정리되어 있는 것과 같이 polystyrene-bpoly(alkyl methacrylate)(PS-b-PAMA) 계열 [18][19][20][21] 및, polystyreneb-poly(butyl acrylate)(PS-b-PBA)의 22 블록공중합체와 poly(butyl acrylate)/polystyrene(PBA/PS), poly(ethylhexyl acrylate)/polystyrene(PEHA/PS) 23…”
Section: 서 론unclassified